PENGGUNAAN AIR FERMENTASI JAGUNG SEBAGAI RAGI ALAMI DALAM PEMBUATAN SOFT ROLL: air fermentasi jagung, ragi alami, soft roll, eksperimen - Ghini Kuntala Devi; Diva Maharani (JURNAL PARIWISATA VOKASI, 2025)
The growing public awareness of healthy lifestyles has encouraged the search for natural food alternatives, including yeast used in bread production. This study aims to examine the use of corn fermentation water as a natural yeast substitute in making soft rolls, replacing commercial yeast that often contains chemical additives. The research employed an experimental method, involving organoleptic tests by both trained and untrained panelists to assess aroma, taste, texture, and color. Nutritional content and shelf life between the experimental and control soft rolls were also compared. The results indicate that natural yeast derived from corn fermentation water produced soft rolls with sensory qualities close to those made with instant yeast, although with a shorter shelf life. In conclusion, corn fermentation water has potential as a viable natural yeast alternative in breadmaking and contributes to the development of healthier, locally-based food innovations.